Uji ketahanan empat varietas tanaman jagung (Zea mays) terhadap intensitas serangan ulat grayak (Spodoptera frugiperda J.E. Smith) - Miftah Dieni Sukmasari; Umar Dani; Andi Dwi Purwana (Fakultas Pertanian Universitas Majalengka, 2023)
The aim of this research was to examine differences in the intensity of armyworm attacks on several varieties of corn plants. This experiment was carried out in Cikalong Village, Sukahaji District, Majalengka Regency. The trial period starts from October 2022 to January 2023. The materials that will be used consist of 4 superior varieties of corn, namely NK 007, Bisi 2, Bisi 18, and Bisi 99. The research method uses a non-factorial Randomized Block Design (RAK) with 4 treatments. repeated 6 times. So the number of experimental plots obtained was 24 experimental plots. The research variables observed included the intensity of armyworm pest attacks, leaf length, number of leaves, leaf area, ear length, ear diameter, weight of husk ear and dry shell weight per ear. To see the effect of treatment, it was tested using the F test at the 5% level. If the calculated F is greater than the F table then the test continues using the LSD (Least Significant Differences) Test. The results of the research showed that the four varieties of corn, namely NK 007, Bisi 18, Bisi 2 and Bisi 99, did not differ significantly in the intensity of attacks by corn armyworm pests, at 14 and 28 HST, number of leaves, leaf width, cob length, diameter. cobs and dry shell weight per cob but were significantly different in the intensity of armyworm attacks at 42 and 56 DAP and the average weight per cob. The Bisi 2 variety provides the most optimal results compared to other varieties planted on average.